Adenoid basal carcinoma of the cervix in a 20-year-old female: a case report - Schnee David; Lingamfelter Daniel; Flauta Victor; DePond William; Menendez Kristyn (BMC, 2006)
Abstract Background Adenoid basal carcinoma of the cervix is a rare condition mostly occurring among postmenopausal women. Although it can be confused with adenoid cystic carcinoma of the cervix, adenoid basal carcinoma has several clinicopathologic features that will allow distinction from adenoid cystic carcinoma. Case presentation This is the case of a twenty-year old African-American female who initially presented with a high-grade squamous intraepithelial lesion on Pap smear, with a subsequent cervical LEEP specimen revealing adenoid basal carcinoma. The lesion showed the characteristic histologic features of adenoid basal carcinoma and was positive for the immunohistochemical marker EMA and negative for collagen IV, further defining the tumor while helping to rule out the possibility of adenoid cystic carcinoma. As far as the authors are aware, this is the youngest reported case of adenoid basal carcinoma to date. Conclusion This case shows that adenoid basal carcinoma can deviate markedly from its typical postmenopausal demographics to affect women as young as 20 years of age. In addition, adenoid basal carcinoma has several identifiable features that will differentiate it from adenoid cystic carcinoma including histologic and cellular morphologies, as well as immunohistochemistry. Treatment for most patients involves hysterectomy, LEEP, or a conization procedure which provides a favorable prognosis because of this lesion's low potential for recurrence and metastasis.